Emergency Department Length of Stay Prior to Surgery in Head Injury Patients - Suryanto Eko Agung Nugroho; Tita Hariyanti; Taufiq Abdullah; Yuddy Imowanto; Dewi Puspitasari (Universitas Muhammadiyah Malang, 2026)
Preoperative delays in traumatic brain injury (TBI) significantly increase morbidity and mortality. While general emergency department (ED) crowding is well-documented, specific bottlenecks bridging ED admission to neurosurgical intervention remain underexplored. This study identifies primary determinants prolonging ED length of stay (LOS) for preoperative TBI patients, offering a novel perspective on systemic versus clinical delays. This retrospective cohort study evaluated 102 head injury patients requiring emergency surgery at Dr. Saiful Anwar Hospital from January 2024 to June 2025. Mean ED LOS was 575.5 minutes (≈9.6 hours). Multivariate linear regression showed that prolonged boarding time and extended diagnostic durations were primary predictors of increased LOS (P < 0.05). Conversely, clinical factors like triage priority and staffing ratios did not significantly influence stay duration (P > 0.05). Notably, boarding time was the most dominant factor, accounting for 40.6% of LOS variance (R² = 0.406). These findings indicate that systemic operational inefficiencies in preoperative waiting and diagnostic workflows are more critical drivers of delay than patient acuity. Consequently, hospital management should prioritize optimizing inter-departmental coordination and emergency surgical pathways to improve outcomes for head injury patients.